Sexual onset and contraceptive use among adolescents from poor neighbourhoods in Managua, Nicaragua. (April 2015) - Decat, Peter; De Meyer, Sara; Jaruseviciene, Lina; Orozco, Miguel; Ibarra, Marcia; Segura, Zoyla; Medina, Joel; Vega, Bernardo; Michielsen, Kristien; Temmerman, Marleen; Degomme, Olivier
Abstract: Background and objectives The prevalence of teenage pregnancies in Nicaragua is the highest in Latin-America. This study aimed to gain insight into factors which determine the sexual behaviours concerned. Methods From July until August 2011, a door-to-door survey was conducted among adolescents living in randomly selected poor neighbourhoods of Managua. Logistic regression was used to analyse factors related to sexual onset and contraceptive use. Results Data from 2803 adolescents were analysed. Of the 475 and 299 sexually active boys and girls, 43% and 54%, respectively, reported contraceptive use. Sexual onset was positively related to increasing age, male sex, alcohol consumption and not living with the parents. Catholic boys and boys never feeling peer pressure to have sexual intercourse were more likely to report consistent condom use. Having a partner and feeling comfortable talking about sexuality with the partner were associated with hormonal contraception. Conclusions Our data identified associates of adolescents' sexual behaviour related to personal characteristics (sex and alcohol use), to the interaction with significant others (parents, partners, peers) and to the environment (housing condition, religion). We interpreted those associates within the context of the rapidly changing society and the recently implemented health system reform in Nicaragua. Chinese Abstract 摘要 背景与目的 尼加瓜拉是拉丁美洲青少年妊娠率最高的国家。本研究旨在深入了解其性行为相关因素。 方法 2011年7月至8月，研究者在马那瓜贫困地区随机抽样，通过入户访视对青少年进行调查。统计方法采用Logistic回归，分析与性发生及避孕相关的影响因素。 结果 研究分析了2 803名青少年的数据。在475名与299名有性活动的男孩与女孩中，分别有43%与54%采取了避孕措施。研究表明，性发生与年龄增长、男性性别、酒精摄入及脱离父母独居等因素呈正相关。天主教男孩与从未感受到性交方面同侪压力的男孩会坚持使用避孕套。有性伴侣且可以与性伴侣坦然讨论性话题与避孕药的使用相关。 结论 研究数据表明，青少年性行为与个人特征（性活动及酒精摄入）、其他个体影响（父母、性伴侣、同侪）以及环境因素（住房条件、宗教）相关。我们认为这些相关性发生的背景为尼加拉瓜瞬息万变的社会环境与近期实施的医疗系统体制的改革。